Islam Lokal: Ruang Perjumpaan Universalitas dan Lokalitas - Ahmad Zainul Hamdi (Universitas Islam Negeri Mataram, 2005)
The contact between universality of Islam and locality of Muslim conditions produces what is called local Islam that is very colorful in accordance with its local contexts. So, to view local Islam apart from normattive Islam is a misleading way, because all communities of local Islam interprate and base their believe and practices in certain and respectively unique way on normative Islam, the Qur’an and the Sunnah. That is why any local Islam belief system and practices such as Islam Jawa, Islam Sasak, Islam Bima etc can not be superficially considered non-Islam This article is focused on Islam Jawa, on the problem of connecting the idea of universality and locality of Islam belief system and practices. There are some issues to be pondered out here as follows: (1) is the Islam Jawa a kind of so issolative Islamic belief system that it has no connection with ather great tradition of Islam in other places ?; (2) wether a unilateral justification on local Islam, Islam Jawa, as an incorrect Islam refer to its real and objective existence or just a matter of mode of interpretation to the sacred texts; and (3) does any popular religious practices of Javaness Muslims merely based on pre-Islamic religions or it has its own normative basis in the Islamic doctrines. Revealing answer to the three issues is extremely important in case that the voice of Islam can not merely be laid on the perspectives of Islamic scholars but those of ordinary Muslims as well. Dealing with the issues lead the author to a conclussion that the Islam Jawa—or any ather sincretics Islam—must be considered a kind of Islamic discourse, substantialism. Such a discourse puts sacred texts as a gateway to a universal goodness from/through which any form of local tradition finds its significance and justification.